Letter from Ernst Winterstein to Georg Bredig, March 1904 - Winterstein, Ernst (1904)
Ernst Winterstein (1865-1949) asks Georg Bredig (1868-1944) to send him a copy of his habilitation thesis on colloidal metals.
Keywords: Bredig, Georg, 1868-1944; Winterstein, Ernst, 1865-1949; Colloids; Chemists; Chemistry, Physical and theoretical